Status of reproductive performance in rural buffaloes artificially inseminated using deep frozen semen - GOKHALE, S B; BHAGAT, R L (The Indian Journal of Animal Sciences, 2013)
Data on 6 762 artificral inserminations on 5 793 village buffaloes belonging to 2 650 farmers spread over 17 villages in Maharastra during June 1991 to September 1996 were analysed for studying reproductive performance in rural buffaloes artifucailly inseminated useing deep frozen semen. The average farmer herd size was of 2.19. The mean conception rate was observed to be 51. 84 +- 0.61%. The local buffalo breeds (Pandharpuri and Nagpuri) exhibited higher conception rate than Murrah or Mehsana breeds. Generally conception rate improved from first lactation (39.36+- 1.61%) to third lactation (56.25+-1.67%) and then declined. Parity, season of insemination, uterine horn tone and AI sequence had significant effect on conception rate. Presence of mature follicle on either right or left ovary, type of vaginal discharge and eve the thawing temperature of water did not affect the extent of conception rate. It was recommended that among other factors, farmer observation on vaginal dischage , vulva swelling, bellowing can be relied upon for improving conception rate.